Study on reaction of subpapillary venous plexus in patients with arterial occlusive diseases of lower extremity by reflective spectrophotometry - Kimura, T; Tsushima, N; Yoshizaki, S; Nakayama, R (Angiology, 1988)
The reactions of the subpapillary venous plexus were observed by analyzed fractional blood volume of tissue (Vb) in patients with arterial occlusive diseases, Fontaine's stage I-II, using the reflective spectrophotometer. The sole skin of 11 normal subjects, 17 patients with arteriosclerosis obliterans (ASO), and 14 patients with thromboangiitis obliterans (TAO) were scanned by the light reflectance of four specially selected wavelengths, including isobestic points (586 and 569 nm) and peaks in the spectra of oxyhemoglobin and deoxyhemoglobin (577 and 560 nm) in referring to time. Sampling area was the subpapillary venous plexus histologically because the depth for receiving reflectance is about 1.0 mm from the sole skin surface. One series observations was divided into five steps depending on the modes of combination of the applied pressure to ankle cuff and tilting. The Kubelka-Munk equation was utilized to calculate blood volume (Vb). It is concluded that the patients with ASO might have a dysfunction, not of the subpapillary venous plexus, but of the venular valve, whereas patients with TAO might have a dysfunction of both the subpapillary venous plexus and venular valve.